2016
DOI: 10.1080/19317611.2016.1204403
|View full text |Cite
|
Sign up to set email alerts
|

Men's Sexual and Relational Adaptations to Erectile Dysfunction After Prostate Cancer Treatment

Abstract: This study investigated how men adapt to erectile dysfunction and other sexual side-effects of prostate cancer treatment. The study recruited nonheterosexual and heterosexual men using an anonymous, international, online survey (N D 558). This article focuses on a qualitative analysis of answers (n D 348) to one open-ended question on sexual practices after treatment. Five themes emerged: (a) recovery of erectile function; (b) reframing sexual practices; (c) the importance of partners; (d) exploring anal sex; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 33 publications
(42 reference statements)
1
31
2
Order By: Relevance
“…GBMPCa have different support needs about the sexual side effects of prostate cancer treatment. For example, GBMPCa who have had a radical prostatectomy have a particular sadness regarding the loss of ejaculate, which some have argued is distinctly central in gay sex (Mitteldorf, 2005;Wassersug, Westle, & Dowsett, 2017). For GBMPCa engaging in receptive anal sex, changes to sensitivity and bowel function or worries about radiation exposure for their partner have direct implications (Nasser, Cohen, Dauer, & Zelefsky, 2016;.…”
mentioning
confidence: 99%
“…GBMPCa have different support needs about the sexual side effects of prostate cancer treatment. For example, GBMPCa who have had a radical prostatectomy have a particular sadness regarding the loss of ejaculate, which some have argued is distinctly central in gay sex (Mitteldorf, 2005;Wassersug, Westle, & Dowsett, 2017). For GBMPCa engaging in receptive anal sex, changes to sensitivity and bowel function or worries about radiation exposure for their partner have direct implications (Nasser, Cohen, Dauer, & Zelefsky, 2016;.…”
mentioning
confidence: 99%
“…What was interesting, though, was the diversity of novel practices and options between those extremes. Data from 348 of the men ( 27 ) confirmed that it was possible for many men to reframe their sexual practices, and that having a supportive sex partner was of major importance for many in exploring new sexual practices.…”
Section: The Relevance Of Iief For Men In the Context Non-erection Dementioning
confidence: 97%
“…Indeed, many manage to find rewarding orgasmic sex even with chronic ED. Survey data from 558 prostate cancer patients provided insights into how both heterosexual and non-heterosexual men’s sexual practices can change as a result of their prostate cancer treatments ( 27 , 120 ). At one extreme, many men asserted that their “ sex life was over ” as a result of iatrogenic ED.…”
Section: The Relevance Of Iief For Men In the Context Non-erection Dementioning
confidence: 99%
See 2 more Smart Citations